Integrasi Literasi Hukum dan Nilai-Nilai Dakwah Islam sebagai Strategi Pemberdayaan Masyarakat untuk Pencegahan Kekerasan dalam Rumah Tangga di Kecamatan Panyabungan, Kabupaten Mandailing Natal - Rahmi Wahyuni; Ardina Khoirun Nisa (Karsa : Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT Domestic violence (DV) remains a persistent social and legal issue in Mandailing Natal Regency, Indonesia, where limited legal literacy and socio-cultural perceptions often hinder prevention efforts and discourage victims from seeking assistance. This community service program aimed to enhance community legal literacy, strengthen Islamic da'wah values in preventing domestic violence, and develop a sustainable community-based prevention mechanism in Panyabungan District. The program adopted a participatory approach through legal education sessions, Focus Group Discussions (FGDs), case-based learning, and community mentoring involving 85 participants, including housewives, religious leaders, community leaders, village officials, and young women. Program effectiveness was evaluated using pre- and post-intervention assessments, participant observations, and discussion outcomes. The results indicated a 73% increase in participants' understanding of Law No. 23 of 2004 concerning the Elimination of Domestic Violence, a 68% improvement in their ability to identify early indicators of domestic violence, and the successful establishment of a Community-Based Domestic Violence Prevention Task Force. The integration of legal education with Islamic da'wah values also fostered a shift in community perceptions, recognizing domestic violence not merely as a private family matter but as a public social issue requiring collective responsibility and intervention. This integrated legal–religious empowerment model demonstrates the potential for strengthening community participation, improving legal awareness, and establishing sustainable domestic violence prevention mechanisms in rural communities.